Literature Review the Influence of Organizational Culture, Human Resource Management and Leadership on Performance - Kusumastuti, Shinta; Syamsunasir, Syamsunasir (Dinasti Publisher, 2025)
This literature review aims to propose a hypothesis concerning the connections between factors for prospective studies in human resource management (HRM). The review focuses on organizational culture, HRM, leadership, and performance, presented as a scientific article in HRM. The study utilizes a descriptive qualitative approach, relying on data obtained from literature reviews and analyses of pertinent previous studies. The data is derived from previous research and academic sources, including Dinasti Publisher, Semantic Scholar, Google Scholar, and digital reference materials. Each independent variable is analyzed using at least one relevant article to ensure reliability. The findings indicate that organizational culture, HRM, and leadership play a crucial role in influencing performance. Positive organizational culture fosters collaboration and innovation, HRM aligns employee potential with organizational goals through effective recruitment, training, and management practices, while leadership inspires and empowers employees to achieve optimal performance. This research emphasizes the significance of incorporating organizational culture, HRM, and leadership to drive exceptional performance and offers insights into how these elements are interconnected in improving both individual and organizational results.